FINANCIAL LITERACY, INFRASTRUCTURAL FACILITY AND FINANCIAL INCLUSION OF MICRO, SMALL AND MEDIUM ENTERPRISE OWNERS IN NIGERIA (Journal of Business Management and Accounting, 2025)
More than two billion micro, small and medium enterprise (MSME) owners worldwide lack access to financial accounts, while others have sporadic use of financial services. Previous efforts to address this issue primarily focused on financial institutions providing affordable banking products. This study examines the effect of financial literacy on financial inclusion as moderated by infrastructural facilities. The study encompasses 11,289 MSME owners in Ondo State, Nigeria, using exploratory research design. Data was analyzed using descriptive statistics and structural equation modeling (PLS-SEM). The findings indicate that independent variables explain 76 percent changes in the dependent variable, with a standardized regression estimate (SRE) of 0.74, significant at 0.05. Additionally, the study finds that infrastructural facilities partially mediate the correlation between independent variables and dependent variable, with coefficient of 0.274, significant at p< 0.05. As a result, the study suggests the implementation of financial inclusion programs, including financial literacy initiatives integrated into school curricula and community programs, to enhance financial knowledge, experience, and awareness among MSME owners in the study areas. Furthermore, the study recommends infrastructural facilities such as mobile phones and mobile internet access to address specific financial inclusion challenges.